Factors Influencing BIM Adoption for Construction Enterprises in China - Ruixue Zhang; Yuyan Tang; Liang Wang; Zeyu Wang (Advances in Civil Engineering)
The construction industry is one of the important pillars of the Chinese national economy. BIM, as a new information technology tool, provides an intelligent digital representation of buildings to support diverse activities and brings about a wide range of benefits throughout the life cycle of projects. However, BIM has not been widely adopted in construction enterprises in China. It is necessary to make a comprehensive and systematic analysis of the influencing factors for BIM adoption. This paper sums up 13 influencing factors from four aspects, namely, technology, economy, institution, and environment aspect. The questionnaire survey and statistical analysis were used to collect and process data which is applied to determine the influencing factors. Based on relevant literature, a hypothesis model was established by the structural equation modeling method. SPSS software and AMOS software were used to test the model. Then, the key factors influencing BIM adoption are induced. The results show that the key factors that influence BIM adoption in China include personnel quality, investment in personnel training, BIM standardization, and the influence of senior managers in the organization. Combined with the above conclusion, this paper puts forward some suggestions for promoting BIM adoption and specific measures to realize the wide application of BIM technology in the Chinese construction industry.